Analisis Perancangan dan Kelayakan Pembukaan Apotek di Kabupaten Cirebon - Suhartoyo, Rivaldo Putra; Chumaidiyah, Endang; Suryana, Nanang (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Fajar Farma Pharmacy is a business operating in the health sector. Fajar Farma sells various health needs, such as medicines and health equipment. Currently, Fajar Farma Pharmacy already has one offline shop to sell its products. Because the income obtained in the last few years is quite satisfactory. To develop the pharmacy business, there are several solutions that can be used to solve problems. Depicted in the fishbone diagram there are 4 problem branches, namely man, facility, market, and method. Based on the problem branch, the solution that will be implemented is opening a new branch due to the existence of a market in Gunung Jati District. Therefore, the owner plans to open a branch shop of Fajar Farma Pharmacy which is located on Jalan Ki Gede Mayung, Gunung Jati District, Buyut Village, Cirebon Regency. In this research, a feasibility analysis was carried out covering 3 aspects, namely market aspects, technical aspects and financial aspects. After carrying out feasibility analysis calculations, the NPV value was IDR 63,638,483, the IRR was 40.61%, the payback period was 3.71 years or 44.55 months. So opening a new pharmacy branch can be said to be feasible. Based on sensitivity calculations, the increase in raw material prices is sensitive at 9.87%, the increase in labor costs is sensitive at 38.42%, while the decrease in demand is sensitive at 7.02%. The results of calculating the feasibility of opening a new branch of Fajar Farma Pharmacy with a MARR of 16.49% show that the NPV is still more than zero, the payback period is still within the investment period, namely 5 years, and the IRR is greater than MARR.